REALISASI PRINSIP KERJASAMA DALAM SEBUAH INTERAKSI - -, M. Jazeri (Diksi, 2015)
This article describes the use and the violation of principles of cooperation or maxims. The maxims are used for some purposes. The maxim of quantity is used to express information clearly, to ask for help, and to avoid misunderstanding. The maxim of quality is used to express true information, to argue an opinion, and to make a conclusion. The maxim of relevance is used to find out true information and to give true information. The maxim of manner is used to express information clearly and to avoid misunderstanding. The violations of the maxims can be done by means of direct violation, opting out, clashing, and flouting. Such violations have some functions. The maxim of quality is violated to raise a comic effect, to hide an intention, to flatter, and to hide embarrassment. The maxim of relevance is violated to raise a conversational implicature and to raise a comic effect. The maxim of manner is violated to hide embarrassment, to raise a comic effect, and to raise a conversational implicature. Keywords: maxims of cooperation, maxim violation